Cost-effectiveness analysis of fidaxomicin for the treatment of Clostridioides (Clostridium) difficile infection in Japan. Issue 6 (June 2020) - Okumura, Hiroyuki; Ueyama, Maki; Shoji, Shingo; English, Marci
Abstract: Background: The cost of treating Clostridioides difficile infection (CDI), particularly recurrent disease, is high. In clinical trials, fidaxomicin has been associated with significantly lower recurrence rates and higher sustained cure rates versus vancomycin. The high acquisition cost of fidaxomicin has limited its acceptance into clinical practice. Objective: To evaluate the cost-effectiveness of fidaxomicin versus vancomycin in patients with CDI after failure of metronidazole in the Japanese healthcare setting. Methods: Clinical results from three phase III trials and inputs based on assumptions validated by clinical experts in Japan were used in a semi-Markov model with 1-year time horizon. Incremental cost-effectiveness ratios (ICERs) for fidaxomicin versus vancomycin were expressed as cost per quality-adjusted life year (QALY) and interpreted using willingness-to-pay thresholds of JPY 5, 000, 000 (primary) and JPY 7, 500, 000 (secondary) per QALY gained in Japan. Probabilistic sensitivity analyses and scenario analyses were performed. Results: Higher drug acquisition costs for fidaxomicin were partially offset by lower hospitalization costs driven by fewer recurrences, lower costs of complications, and fewer general practitioner visits versus vancomycin. The ICER for fidaxomicin versus vancomycin was estimated at JPY 5, 715, 183 per QALY gained. Sensitivity analyses showed a 46% probability of fidaxomicin being cost-effective versus vancomycin at a willingness-to-pay threshold of JPY 5, 000, 000 per QALY gained. At a threshold of JPY 7, 500, 000, there was a 54% probability of fidaxomicin being cost-effective. Conclusions: Fidaxomicin treatment in patients with CDI following failure of metronidazole improves health outcomes with partial offset of higher drug acquisition costs versus vancomycin.